Growth of Local Native Chickens in the Grower Phase Supplemented with Leucine - Sandra Meol; Charles Venerius Lisnahan; Theresia Ika Purwantiningsih (Journal of Tropical Animal Science and Technology, 2026)
The purpose of this study was to determine the effect of leucine supplementation in feed on the growth of native chickens in the grower phase. This study was conducted in the native chicken coop of the Unggas Jaya Farmers Group, Sasi Village, Kefamenanu city District, North Central Timor Regency. This study was conducted for 3 months, from September to November 2025, while chicks (DOC - 6 weeks) were raised from July 2025. The livestock used in this study were 80 native chickens aged 6 weeks. This study used a Completely Randomized Design (CRD) method. Chickens were randomly assigned to 4 treatments with 4 replications, each consisting of 5 chickens. The treatments given were: T0: control feed without L-leucine, T1: control feed + 0.30% L-leucine, T2: control feed + 0.50% L-leucine and T3: control feed + 0.70% L-leucine. The variables observed were body weight gain, feed consumption and feed conversion ratio. Data were analyzed using Analysis of Variance and continued with Duncan's test. The results showed that body weight gain for treatments T0, T1, T2 and T3 were 94.83±1.24, 98.13±8.92, 102.91±1.34 and 106.29±2.11 g/head/week, respectively. Feed consumption was 450.09±7.84, 462.50±8.92, 480.16±13.70, and 488.22±7.47 g/bird/week, respectively. Feed conversion ratio was 4.77±0.06, 4.71±0.03, 4.67±0.12, and 4.60±0.03, respectively. Statistical analysis showed that the treatments significantly affected body weight gain, feed consumption, and feed conversion ratio (P<0.05). It was concluded that leucine supplementation in the feed significantly affected body weight gain, feed consumption, and feed conversion ratio. Supplementation of 0.70% leucine in the feed provided the maximum effect on body weight gain, feed consumption, and feed conversion.